2000
DOI: 10.1001/archopht.118.6.773
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Varying Radiation Doses in the Treatment of Choroidal Melanoma

Abstract: To determine if a reduction in proton radiation dose from the standard dose of 70 cobalt gray equivalents (CGE) to 50 CGE would decrease radiation-induced complications, thereby improving visual prognosis, without compromising local tumor control for patients with uveal melanoma at high risk of these complications.Design: Randomized, double-masked clinical trial.Participants: A total of 188 patients with small or medium-sized choroidal melanomas (Ͻ15 mm in diameter and Ͻ5 mm in height) near the optic disc or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(27 citation statements)
references
References 80 publications
4
19
0
Order By: Relevance
“…Recurrence of the primary tumour after radiation or local resection is another problem. UM recurrence rates up to 15% after radiation therapy (including plaques and proton beam therapy) have been reported [2, 4, 5, 6, 7]. With local resection, Shields et al [8]have reported an 11% recurrence rate for ciliary body and choroidal tumours, and for iris melanomas, we found that recurrence rates of 8–11% have been reported [9, 10].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Recurrence of the primary tumour after radiation or local resection is another problem. UM recurrence rates up to 15% after radiation therapy (including plaques and proton beam therapy) have been reported [2, 4, 5, 6, 7]. With local resection, Shields et al [8]have reported an 11% recurrence rate for ciliary body and choroidal tumours, and for iris melanomas, we found that recurrence rates of 8–11% have been reported [9, 10].…”
Section: Introductionsupporting
confidence: 58%
“…transpupillary thermotherapy), proton therapy or plaque radiotherapy. Although effective, these treatments are associated with significant sight-threatening morbidity including a high incidence of radiation retinopathy (80%), macula oedema, scarring and haemorrhage [2, 3]. Recurrence of the primary tumour after radiation or local resection is another problem.…”
Section: Introductionmentioning
confidence: 99%
“…Favorable 5-year and 10-year local failure rates of 3.2% and 4.3%, respectively, were observed (43). For uveal melanoma, doses of 60 Gy delivered in four daily fractions of 15 Gy have been highly effective (44). Based on an analysis of 2069 patients treated at Harvard Cyclotron Laboratory and Proton Therapy Center at Massachusetts General Hospital between 1975 and 1997, a 15-year local control rate is 95% and the rate of eye preservation is 84%.…”
Section: Definitive Rt For Ocular Melanomasmentioning
confidence: 99%
“…However, there was no advantage with respect to mortality or enucleation when comparing particle therapy and brachytherapy (45). Dose reduction may be important for toxicity reduction in particle therapy as it is in brachytherapy, and a prospective randomized trial of lower-dose (50 Gy) versus standard dose (70 Gy) proton radiation for small-to-moderate sized uveal melanoma showed no differences in a 5-year local or systemic recurrence or visual acuity loss, suggesting lower dose may be acceptable moving forward (44). In the past decade or two, linear accelerator (LINAC) stereotactic RT (SRT), or SRS with either LINAC or gamma knife has been investigated for its potential as an alternative option to proton beam (46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Definitive Rt For Ocular Melanomasmentioning
confidence: 99%
“…Based on available evidence, the group concluded that proton therapy provided at least incremental net health benefits for patients with ocular tumours, central nervous system tumours, paediatric cancers or tumours within previously irradiated areas of the body. [9][10][11][12][13][14] In their final recommendations, treatment with proton therapy is recommended as a covered benefit for patients with these specific conditions, but not for others. With the exception of ocular tumours, these recommendations are not based upon randomised evidence but instead are based upon the lack of judged clinical equipoise in select patient groups which was deemed likely to prevent the conduct of prospective randomised trials.…”
mentioning
confidence: 99%